Ectopic Pregnancy in a Cesarean Section Scar: Successful Management Using Vacuum Aspiration under Laparoscopic Supervision—Mini Review of Current Literature - Mustafa Koplay; Nasuh Utku Dogan; Mesut Sivri; Hasan Erdogan; Selen Dogan; Cetin Celik (Case Reports in Surgery)
A cesarean scar ectopic pregnancy (CSEP) is a fairly uncommon presentation wherein the conceptus is implanted deep in the myometrium and at the exact scar site of the previous cesarean section. There are various CSEP management options that range from medical treatment to surgical interventions such as dilatation and curettage, laparoscopic excision, resection by laparotomy, or, sometimes, a combination of these modalities. Establishing a diagnosis of CSEP can be challenging. Given the relatively rare incidence of CSEP, its management is controversial and current standards of therapy have been derived from data obtained from a limited number of patients. Herein, we present transvaginal ultrasonography (TVUS) imaging findings and management strategies used in a case of CSEP along with the short review of current literature.